Guinea-Bissau : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2005)
This Selected Issues and Statistical Appendix paper analyzes recent economic developments in Guinea-Bissau. The paper highlights the structural problems that will need to be addressed over the next few years if Guinea-Bissau is to break through the downward spiral of declining economic activity, increasing poverty, and political instability. The paper examines the real, fiscal, and monetary sectors in Guinea-Bissau. It also provides an overview of recent developments in the balance of payments and highlights Guinea-Bissau's severe external debt problem.